Effects of online flipped classroom on foreign language classroom anxiety and reading anxiety. Issue 4 (4th May 2023) - Gok, Duygu; Bozoglan, Hilal; Bozoglan, Bahadir
Abstract: In this study, we aimed to integrate the flipped classroom model into "Advanced Reading and Writing" course and to investigate the effect of the flipped classroom model on pre-service English language teachers' foreign language classroom anxiety (FLCA) and foreign language reading anxieties (FLRA). This study involved two groups (34 in the flipped group and 32 in the non-flipped group) of first-year English language teachers in Turkey. Within this framework, Foreign Language Classroom Anxiety Scale and Foreign Language Reading Anxiety Scale were employed to determine pre-service English language teachers' FLCA and FLRA levels before and after the treatment in the flipped and the non-flipped groups comparatively. There was a significant decrease in the FLCA and FLRA levels in the flipped group. However, there was no significant change in the non-flipped group. Supplemental data for this article is available online at https://doi.org/10.1080/09588221.2021.1950191 .